Parental Perception Of Early Childhood Educational Involvement: Research Evidence Of The Mfanstiman District Of The Central Region Of Ghana - Jinapor, Ahmed; Larbi-Appiah, Naa Korkor (Advances in Social Sciences Research Journal, 2020)
This study is a quantitative research hinged on the descriptive study paradigm where perspectives of selected parents of pupils at the early childhood level at the Anomabo Circuit “A” in the Mfantsiman Municipality of the Central Region of Ghana were sought on how parental involvement is shaped in their localities, the extent of their involvement in their children education, and challenges they confront in this direction. Using descriptive and inferential statistics such as means and standard deviations, findings from the study among others revealed that parents perceived the school as a place for teachers to be in charge; though the results that emanated from the study points to parent participants of this study being involved in their children’s education. On the issue of challenges that confronts parents in the involvement of their children’s education at the early childhood level, also an objective that informed the study, the results among others include; lack of financial resources, and time constraints and busy schedules. Again, as part of recommendations in the advancement of parental involvement at the early childhood level in Ghana, the study among others calls for robust education and prescription of how parents can and should be involved in their children education.